Remittances, financial development, and growth - Paola Giuliano; Marta Ruiz-Arranz (Institute for the Study of Labor (IZA), 2006)
Despite the increasing importance of remittances in total international capital flows, the relationship between remittances and growth has not been adequately studied. This paper studies one of the links between remittances and growth, in particular how local financial sector development influences a country's capacity to take advantage of remittances Using a newly-constructed dataset for remittances covering about 100 developing countries, we find that remittances boost growth in countries with less developed financial systems by providing an alternative way to finance investment and helping overcome liquidity constraints. The study also explores some common myths about remittances and suggests that they are predominantly profit-driven and mostly pro-cyclical.
Keywords: F22; F43; O16; 330; remittances; financial development; growth; Rücküberweisung (Migranten); Finanzsektor; Wirtschaftswachstum; Welt